2021
DOI: 10.21203/rs.3.rs-163730/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Target Position and Safety Margin Effects on Path Planning in Obstacle Avoidance

Abstract: This study examined how people choose their path to a target, and the visual information they use for path planning. Participants avoided making contact with an obstacle as they walked to a bookcase and picked up a cup from different locations on a shelf. Participants chose a path with a smaller deviation angle from a straight line to the target and chose a side of the obstacle which was closer to them. Unlike previous studies which have not included a safety margin in their analyses, we found that the right a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to the study, falls are more common among white people compared with minorities and among those with higher educational levels compared with those with lower educational levels. 21,25 Another possible limitation of the study is the use of self-reported measures of falls. Even though all participants were cognitively normal (CDR 0) and fall ascertainment methods were intensive, underreporting of falls cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study, falls are more common among white people compared with minorities and among those with higher educational levels compared with those with lower educational levels. 21,25 Another possible limitation of the study is the use of self-reported measures of falls. Even though all participants were cognitively normal (CDR 0) and fall ascertainment methods were intensive, underreporting of falls cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies have revealed that a signal from a body part, such as a gaze, serves as an indicator to predict the avoidance direction (Joshi et al, 2021;Nummenmaa et al, 2009;Saeedpour-Parizi et al, 2021). For example, the gazing direction of a person who approaches head-on affects his/her trajectory (Nummenmaa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%